Demokratisasi Pendidikan dalam Pendidikan Islam - M. Iqbal; Paizaluddin; Sabriadi (CONTEMPLATE: Jurnal Ilmiah Studi Keislaman, 2022)
This study aims to describe the democratization of education in Islamic education. The method in this research is a qualitative approach with the of literaturestudy research. Data collection is abtained through observing related literature. Then take an interpretation approach by examining data on objective evidence, to achieve authentic truth. Interpretation here is the material or data that has been described, the interpreted and re-analized to show clarification about the democratization manner. Educational democracy is a system that prioritizez rights and obligations as well as equal treatment for every citizen in education. The role of education in state life will provide many dimensions of nation character building. The principle of democracy can be implemented in the Islamic education system, because basically Islam gives freedom to individuals (students) to develop natural values that exist in them in adapting to the times. The democratization of education in Islamic aeducation is reflected in several aspects including First, Tawhid: The paradigma of freedom. Second, Shura: A vehicle for openness. Third, good deeds, piety, and ulul albab Fifth, Tawassut iprinciple. The principle of moderation. Sixth. Obligations and human rights in the development of science